2015
DOI: 10.1075/eww.36.1.02pet
|View full text |Cite
|
Sign up to set email alerts
|

Response to Davies and Fuchs

Abstract: The Global Web-based English Corpus (GloWbE) introduced to EWW readers in Davies and Fuchs's focus article is an outstanding addition to the corpora of the English-speaking/English-using world -by its sheer size and up-to-dateness, and especially its inclusion of 14 "new Englishes" and six "core Englishes" (i.e. both indigenized and settler varieties, in Schneider's (2007) terminology). 1 Its 1.9 billion words come from 340,000 websites and blogs with the relevant regional suffixes, which were also carefully c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 9 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…However, the same search in the spoken component of several ICE corpora showed that the frequency of these items was much higher in this corpus than in GloWbE. Hence, the working hypothesis has been that, though blogs are partly oral and informal, there is no substitute for actual conversation (as implied by Mair : 30–1 and Peters : 42).…”
Section: Orality and Informality Of Blogsmentioning
confidence: 83%
“…However, the same search in the spoken component of several ICE corpora showed that the frequency of these items was much higher in this corpus than in GloWbE. Hence, the working hypothesis has been that, though blogs are partly oral and informal, there is no substitute for actual conversation (as implied by Mair : 30–1 and Peters : 42).…”
Section: Orality and Informality Of Blogsmentioning
confidence: 83%
“…Perhaps the most major change of contents for second generation corpora is the recommendation for the inclusion of a new component of electronic texts, totalling up to 500,000 words, making the total maximum size of a second generation corpus 1.5 million words. Indeed, from her thorough comprehensive comparison between ICE and the GloWbE corpus of blogs and websites (Davies, ), Loureiro‐Porto (, p. 468) concludes that ‘the future of ICE should include web registers alongside the text types included so far’; from other comparisons, similar conclusions are drawn by Mair (), Mukherjee (), Nelson () and Peters (), in their responses to Davies and Fuchs (). A list of possible electronic texts is presented in Appendix 3 for discussion.…”
Section: Second Generation Corporamentioning
confidence: 79%
“…The issue of sampling was also raised. (2015), Mukherjee (2015), Nelson (2015) and Peters (2015), in their responses to Davies and Fuchs (2015). A list of possible electronic texts is presented in Appendix 3 for discussion.…”
Section: Spoken and Written Textsmentioning
confidence: 99%
“…Just as Davies and Fuchs have admitted, ‘regarding genre, of course GloWbE simply represents whatever is found on the web, and therefore it may include very little from certain genres’ (Davies & Fuchs, 2015a, p. 45). In terms of text source, ‘ all subcopora [of GloWbE] constitute representative samples of how these national varieties of English are used in web‐based communication’ (Davies & Fuchs, 2015b, p. 4), but it still remains unclear how far the web‐based discourse could represent characteristics of a prototypical average speaker of each variety (Cook & Hirst, 2012; Loureiro‐Porto, 2017; Peter, 2015), how much internet language should each linguistic variety be comprising, and to what extent is blogging discourse resembling spontaneous and authentic conversation (Mair, 2015; Peter, 2015).…”
Section: Findings and Discussionmentioning
confidence: 99%